Dukken som animeret billede – mellem idolatri og idollatry, mellem dukkekult og dukkekærlighed: Dukken som animeret billede – mellem idolatri og idollatry, mellem dukkekult og dukkekærlighed - Jørgensen, Hans Henrik Lohfert; Leth-Espensen, Pernille; Skinnebach, Laura Katrine (Periskop – Forum for kunsthistorisk debat, 2022)
ABSTRACT In 2020, the annual seminar at Art History in Aarhus was dedicated to a category of images usually absent from art historical research: dolls and puppets. The premise of the seminar was that through their animation, dolls or puppets are a universal, albeit historical, kind of image across all visual and anthropological cultures. A doll may be defined as an interactive, animated, representational figure, tangible and usually anthropomorphic. Dolls and puppets are closely related to other three-dimensional images, such as statues, sculptures, fetishes, and idols, but they have been unduly marginalized within art history due to their lowly associations with the childish and the feminine, with play and palpable interactivity rather than disengaged aesthetic contemplation. In this playful primer in pupalogy, we approach art historiography from the animated and ludic perspective of the doll. We engage with dolls in order to learn more about their history and historiography, their forms of animation, scale, etymology, materiality, and liminal status between life and death. The article thus toys with the deepest heritage of the image: its animation, its play, and its ludic interactions.